Breeding performance with special reference to pre-weaning mortality of C57BL/6 and B6D2F1 hybrid strain of mice maintained at ACTREC Animal Facility (Journal of Laboratory Animal Science, 2024)
Successful breeding programme of laboratory animals is one of a key factor in any facility operations. In-house breeding  of laboratory animal species depends on using correct breeding method, number of animals requested by the researchers,  litter size, birth weight, perinatal mortality, weaning percentage, female:male ratio, parity interval, fostering, postpartum  heat, non-productive breeders, enrichment programme etc. To fulfil the animal demands for in vivo research, these points  play significant role, especially perinatal mortality. Perinatal mortality is strain dependent and therefore facility must be  aware about the percentage of pups mortality to avoid further miscalculation while setting up the breeding program. In  order to get the first hand information about strain wise perinatal mortality, historical control data or baseline data should  be generated which play an important role in successful breeding programme and timely meeting the target of providing  experimental animals. Aim of the present study was to generate baseline control values of reproductive efficiency parameters  of commonly used mice strains at ACTREC Animal Facility. The existing in-house data was compiled for the period of  July to December 2019. Perinatal mortality varied between the primiparous and multiparous females. In total, data of 4247  pups obtained from 39 inbred primiparous, 93 outbred primiparous, 159 inbred multiparous and 466 outbred multiparous  females. The average number of pups delivered by inbred primiparous and multiparous females was recorded as 5.13 and  5.85, respectively. There was no significant difference between the female:male ratio between primiparous and multiparous  females of C57BL/6 inbred strain. Weaning of pups was done on day 21. Percentages of weaning of pups from primiparous  and multiparous inbred strain were recorded as 87 and 92.37%, respectively. Perinatal mortality in inbred primiparous  female was 13% while in inbred multiparous was 7.63%. It is observed that perinatal mortality in inbred primiparous pups  is higher than inbred multiparous females. In case of outbred stock of C57BL/6 mice, we observed average litter born of  4.96 and 5.70 for primiparous and multiparous mothers, respectively. Weaning percentage of 83.73% and 93.56% was  recorded in outbred primiparous and multiparous mothers, respectively. Perinatal mortality in pups obtained from outbred  primiparous and multiparous mothers was 15.84% and 6.44% respectively. The data indicated that perinatal mortality is  significantly high in the pups obtained from primiparous females than multiparous females of both the breeding methods.  We compared the data of C57BL/6 mice with robust strain, B6D2F1. The overall results can be used as baseline data for our  C57BL/6 and B6D2F1 strains by the ACTREC scientists as well as colony managers from other facilities.
Keywords: Breeding performance; pre-weaning mortality; C57BL/6 and B6D2F1 mice